Late-Onset Acute Kidney Injury is a Poor Prognostic Sign for Severe Burn Patients - You, Bo; Yang, Zichen; Zhang, Yulong; Chen, Yu; Gong, Yali; Chen, Yajie; Chen, Jing; Yuan, Lili; Luo, Gaoxing; Peng, Yizhi; Yuan, Zhiqiang (Frontiers in Surgery, 2022)
Introduction: Acute kidney injury (AKI) is a morbid complication and the main cause of multiple organ failure and death in severely burned patients. The objective of this study was to explore the epidemiological characteristics, the risk factors, and impact of both early and late AKIs, respectively. Methods: This retrospective study was performed with prospectively collected data of severely burned patients during 2011-2017. AKI was diagnosed according to Kidney Disease Improving Global Outcomes (KDIGO) criteria (2012), and it was divided into early and late AKIs depending on its onset time (within the first 3 days or >3 days post burn). The baseline characteristics, clinical data, and outcomes of the three groups (early AKI, late AKI and non-AKI) were compared using logistic regression analysis. Mortality predictors of patients with AKI were assessed. Results: A total of 637 patients were included in analysis. The incidence of AKI was 36.9% (early AKI 29.4%, late AKI 10.0%). The mortality of patients with AKI was 32.3% (early AKI 25.7%, late AKI 56.3%), and that of patients without AKI was 2.5%. AKI was independently associated with obviously increased mortality of severely burned patients [early AKI, OR = 12.98 (6.08-27.72); late AKI, OR = 34.02 (15.69-73.75)]. Multiple logistic regression analysis revealed that age, gender, total burn surface area (TBSA), full-thickness burns of TBSA, chronic comorbidities (hypertension or/and diabetes), hypovolemic shock and tracheotomy were independent risk factors for both early and late AKIs. However, sepsis was only a risk factor for late AKI. Conclusions: AKI remains prevalent and is associated with high mortality in severely burned patients. Compared with early AKI, late AKI has a lower occurrence rate, but greater severity and worse prognosis. Late AKI is a poor prognosis sign in severe burns.